Feasibility and experience of nurse-led ultrasound-guided percutaneous liver biopsy - Farrington, Elizabeth Anne (Frontline Gastroenterol, 2012)
The demand for collaborative and innovative clinical practitioners to act as leaders in healthcare remains strong as many challenges are faced including rising costs, shortage of professionals, the introduction of new technology and difficulties with access to care. Nurses in advanced nursing practice are well positioned to respond to this, playing a key role in building nursing knowledge, advancing the nursing profession and contributing to sustainable and effective healthcare systems. Percutaneous liver biopsy (PLB) is an essential tool used for diagnosis and management in liver disease, being most commonly performed by consultant gastroenterologists, hepatologists and radiologists. While invasive and with complications PLB is a simple, cost-effective procedure that can be undertaken at the bedside. Our study demonstrates that an advanced nurse practitioner (ANP) with a sound working knowledge of hepatology and familiarity with indications, methods and risks of PLB procedure can be trained to perform ultrasound-guided liver biopsy both safely and effectively.